2021
DOI: 10.3389/fmicb.2021.702909
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Salmonella enterica Serovar Rissen From Humans, Food Animals, and Animal-Derived Foods in China, 1995–2019

Abstract: Salmonellosis represents a growing threat to global public health. Salmonella enterica remains the leading cause of bacterial foodborne diseases in China. Salmonella enterica serovar Rissen (S. Rissen) has been recognized as one of the emerging serovars among humans in different countries worldwide. However, knowledge on the prevalence of S. Rissen in China is largely lacking. To address essential epidemiological information for S. Rissen in China, a total of 1,182 S. Rissen isolates recovered from samples acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…It is, therefore, vital to examine the resistance patterns and the genetic basis of antimicrobial resistance in Salmonella, with a focus on MDR, to better manage and contain infections. Notably, the serovars S.1,4, [5],12:i:-and S. Rissen have gained recognition as emerging threats to human health in various countries (3)(4). There remains, however, a substantial gap in the understanding of these serovars' resistance profiles in China, particularly in Guangzhou.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, vital to examine the resistance patterns and the genetic basis of antimicrobial resistance in Salmonella, with a focus on MDR, to better manage and contain infections. Notably, the serovars S.1,4, [5],12:i:-and S. Rissen have gained recognition as emerging threats to human health in various countries (3)(4). There remains, however, a substantial gap in the understanding of these serovars' resistance profiles in China, particularly in Guangzhou.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our findings suggest that Rissen is a common serovar infecting pigs from the region. Although this serovar is thought to have emerged in SE Asia, it has likely spread around the world though global pork markets (Elbediwi et al, 2021) and the European Food Safety Authority (EFSA) and European Centre for Disease Prevention and Control (ECDC) reported it among the top twenty Salmonella serovars linked with human salmonellosis (E.F.S.A, 2017; Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the Rissen serovar is currently one of the emerging serovars in various countries worldwide. In a large-scale global review by Elbediwi et al (2021), it was revealed that the bulk of Rissen isolates (~2/3) were obtained from human samples, more than half of which were asymptomatic individuals. While most non-clinical Rissen isolates in global studies were associated with poultry and porcine samples, several studies have also found the serovar in seafood (Atwill and Jeamsripong, 2021;Lozano-León et al, 2022), and other sources (Prasertsee et al, 2019;Silveira et al, 2019;Nguyen et al, 2021;Sanguankiat et al, 2023).…”
Section: Serovarsmentioning
confidence: 99%